World War I : the global revolution - Sondhaus, Lawrence, 1958- (Cambridge ; New York : Cambridge University Press, 2011)
"World War One was the cause, catalyst, trigger, and accelerator of revolutionary change on an unprecedented scale. This is an indispensable new introduction to the global history of the conflict and its revolutionary consequences from the war's origins to the making of peace and across all of its theatres, including the home fronts and the war at sea. Lawrence Sondhaus sets out a new framework for understanding key themes such as the war aims which inspired the belligerents, the technological developments that made the war so deadly for those in uniform, and the revolutionary pressures that led to the collapse of the Romanov, Habsburg, and Ottoman empires. He also highlights the war's transformative effects on societal norms and attitudes, gender and labour relations, and international trade and finance. The accessible narrative is supported by chronologies, personal accounts, guides to key controversies and debates, and numerous maps and photographs"--
The world in 1914 and the origins of the war -- The July Crisis, 1914 -- The European war unfolds, August-December 1914 -- The world war : East Asia, the Pacific, Africa -- The deepening stalemate : Europe, 1915 -- Essay chapter: Daily life in Anzac Cove -- The home fronts (1914-1916) -- Essay chapter: The trenches and trench warfare -- Raising the stakes : Europe, 1916 -- Essay chapter: With Lenin aboard the "sealed train" -- Upheaval and uncertainty : Europe, 1917 -- The war at sea (1915-1918) -- Essay chapter: Daily life aboard a U-boat -- The US enters the war -- The home fronts (1916-1918) -- The world war : the Middle East and India -- Essay chapter: The legacy of the trenches : mind, body, spirit -- Endgame : Europe, 1918 -- The Paris Peace Conference -- Legacy -- Conclusion.
Includes bibliographical references and index.
ENH
Trim Education
Keywords: World War, 1914-1918.; World politics, 1900-1918.; HISTORY -- Modern -- 20th Century; Social change -- History -- 20th Century; English language